NMR of Proteins and Small Biomolecules - Zhu, Guang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
J. L. Stark R. Powers Application of NMR and Molecular Docking in Structure-Based Drug Discovery O. Vinogradova J. Qin NMR as a Unique Tool in Assessment and Complex Determination of Weak Protein-Protein Interactions K. Chen N. Tjandra The Use of Residual Dipolar Coupling in Studying Proteins by NMR H. Li H. Sun NMR Studies of Metalloproteins R. Ishima Recent Developments in 15N NMR Relaxation Studies that Probe Protein Backbone Dynamics T. Qureshi N. K. Goto Contemporary Methods in Structure Determination of Membrane Proteins by Solution NMR X. Zhao Protein Structure Determination by Solid-State NMR K. H. Sze Q. Wu H. S. Tse G. Zhu Dynamic Nuclear Polarization: New Methodology and Applications
J. L. Stark R. Powers Application of NMR and Molecular Docking in Structure-Based Drug Discovery -- O. Vinogradova J. Qin NMR as a Unique Tool in Assessment and Complex Determination of Weak Protein-Protein Interactions -- K. Chen N. Tjandra The Use of Residual Dipolar Coupling in Studying Proteins by NMR -- H. Li H. Sun NMR Studies of Metalloproteins -- R. Ishima Recent Developments in 15N NMR Relaxation Studies that Probe Protein Backbone Dynamics -- T. Qureshi N. K. Goto Contemporary Methods in Structure Determination of Membrane Proteins by Solution NMR -- X. Zhao Protein Structure Determination by Solid-State NMR -- K. H. Sze Q. Wu H. S. Tse G. Zhu Dynamic Nuclear Polarization: New Methodology and Applications.
Keywords: Chemistry; Bioorganic chemistry; Biochemistry; Chemistry; Bioorganic Chemistry; Protein Science; Bioorganic Chemistry